2009
DOI: 10.1111/j.1365-2966.2008.14290.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards quantitative control on discreteness error in the non-linear regime of cosmologicalN-body simulations

Abstract: The effects of discreteness arising from the use of the N‐body method on the accuracy of simulations of cosmological structure formation are not currently well understood. In the first part of this paper, we discuss the essential question of how the relevant parameters introduced by this discretization should be extrapolated in convergence studies if the goal is to recover the Vlasov–Poisson limit. In the second part of the paper, we study numerically, and with analytical methods developed recently by us, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 69 publications
4
51
0
Order By: Relevance
“…This does not test the scalar mode of the stress tensor though, which ends up inducing the largest correction to the PPF approximation. In this respect, it would be interesting to test how robust the scalar part of the stress tensor is to details of the numerical simulations, as spurious effects due to discreteness may amplify velocity dispersion in simulations [56,57] (see also [58]). …”
Section: Discussionmentioning
confidence: 99%
“…This does not test the scalar mode of the stress tensor though, which ends up inducing the largest correction to the PPF approximation. In this respect, it would be interesting to test how robust the scalar part of the stress tensor is to details of the numerical simulations, as spurious effects due to discreteness may amplify velocity dispersion in simulations [56,57] (see also [58]). …”
Section: Discussionmentioning
confidence: 99%
“…The study of this problem for these initial conditions thus allow one to understand some of the subtleties which may be involved in practically testing for collisionality effects in N body systems. This is in principle an important issue in cosmological simulations (see [1] for a detailed discussion). This proceedings essentially summarizes synthetically results reported in much greater detail in [2].…”
Section: Introductionmentioning
confidence: 99%
“…We note that most of the discussion in the literature has focused the attention on the role of the softening length (see e.g. Splinter et al 1988;Heitmann et al 2005;Romeo et al 2008;Joyce et al 2009a;Power et al 2003): here we have found that a crucial parameter is also represented by the time-stepping accuracy.…”
Section: Discussionmentioning
confidence: 62%
“…However, it is not a simple issue to control the numerical accuracy of the non-linear gravitational clustering in a cosmological simulation; for instance the question of determining the optimal spatial resolution, i.e. the best value for the gravitational force softening length, is still an open problem (see e.g., Splinter et al 1988;Power et al 2003;Romeo et al 2008;Joyce et al 2009a).…”
Section: Introductionmentioning
confidence: 99%